Enhancement Of Transmission Control Protocol Performance Over Low Earth Orbit Satellite Links - Mustafa, Mayada Salih Abdalla (2003)
Recent growth of the Internet has led to the development of Internet services everywhere and over every possible communications medium. Here, Low Earth Orbit (LEO) Satellite has been addressed as a medium for supporting services based on the Transmission Control Protocol (TCP). Basically, TCP was proposed as a common transport protocol for the Internet. The TCP mechanisms have been modified overtime and almost standardized for wired networks. However, for wireless communications still further modifications are needed for TCP mechanisms. Particularly, in this study an Enhanced Selective Acknowledgement (ESACK) mechanism has been proposed to improve the performance of TCP over LEO satellite links. The ESACK detects the network congestion and adjusts the transmission window by considering losses in two consecutive windows.